Validation Information System Munaqasyah Exam Registration Based Android - Alda, Muhamad; Sibarani, Fathiyah Hasyifah; Nasution, Aspiraikhani (Sinkron : jurnal dan penelitian teknik informatika, 2022)
The information systems study program (SI Study Program) Faculty of science and technology is one of the study programs at the State Islamic University of North Sumatra, Medan. Based on the Decree of the Chancellor of the State Islamic University of North Sumatra Medan Number 417L of 2016 concerning the Enforcement of SOPs for the Implementation of the Munaqasyah Exam. The Munaqasyah exam is the last test that must be passed by State Islamic University of North Sumatra, Medan students before obtaining a bachelor's degree (S1) about being responsible for scientific work which is the result of research that has been done. The registration process for the Munaqasyah exam in the information systems study program uses google forms so that students have difficulty getting information about the registration status and the information systems study program must first collect data and student registration documents and carry out validation. By doing this, the registration and validation process for the Munaqasyah exam will be no more effective and efficient. The purpose of this study is to build an android-based information system that can be used to register for the Munaqasyah exam and validate the registration. The system development method used is Extreme Programming (XP) while in designing the system the author uses UML (Unified Modeling Language). In the development of information systems, the author uses Kodular and google spreadsheet databases. With the information system, it is hoped that the registration process and registration validation will be more effective and efficient